2020
DOI: 10.1007/s10926-020-09874-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Long-Term Sickness Absence and Identifying Subgroups Among Individuals Without an Employment Contract

Abstract: Purpose Today, decreasing numbers of workers in Europe are employed in standard employment relationships. Temporary contracts and job insecurity have become more common. This study among workers without an employment contract aimed to (i) predict risk of long-term sickness absence and (ii) identify distinct subgroups of sick-listed workers. Methods 437 individuals without an employment contract who were granted a sickness absence benefit for at least two weeks were followed for 1 year. We used registration dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
4
0
1
Order By: Relevance
“…Prediction models for risk of LTSA among non-sick-listed workers show adequate calibration but poor-to-moderate discrimination with AUCs varying between 0.68 (4) and 0.76 (6). Among sick-listed unemployed workers, Louwerse et al (8) reported discrimination by a three-predictor (educational level, expected sickness absence duration, and help-seeking ability) model, with an over-optimism adjusted AUC of 0.76. The Long-term sickness absence predictions present study confirms that workers with an increased risk of LTSA can be identified early after sick-listing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction models for risk of LTSA among non-sick-listed workers show adequate calibration but poor-to-moderate discrimination with AUCs varying between 0.68 (4) and 0.76 (6). Among sick-listed unemployed workers, Louwerse et al (8) reported discrimination by a three-predictor (educational level, expected sickness absence duration, and help-seeking ability) model, with an over-optimism adjusted AUC of 0.76. The Long-term sickness absence predictions present study confirms that workers with an increased risk of LTSA can be identified early after sick-listing.…”
Section: Discussionmentioning
confidence: 99%
“…LTSA is more prevalent and may be better predicted among workers who report sick. Recently, Louwerse et al ( 8 ) developed an LTSA prediction model for sick-listed individuals without an employment contract. In The Netherlands, unemployed individuals report sick to UWV, the Dutch social security agency.…”
mentioning
confidence: 99%
“…Вероятность зачисления возрастает среди менее образованных, неженатых, вдовых, бездетных, представителей не европеоидной расы [17,28,6]. У лиц с высшим образованием и заявителей молодого возраста (от 20 до 34 лет) всё чаще встречаются расстройства нервной системы и психики 1 [22,24]. В целом лица моложе 45 лет, с лучшими профессиональными навыками для трудовой деятельности, реже зачисляются в программы [18].…”
Section: социальное обеспечение: взаимодополняемость и охват помощьюunclassified
“…However, the longer individuals are absent from work, the less likely they are to return [42][43][44]. A prediction model for workers who have just recently been sick-listed can help occupational health professionals to target individuals at risk of long-term sickness absence and identify effective early interventions [45,46]. From a rehabilitation point of view, such a tool could have more impact.…”
Section: Implications For Research and Practicementioning
confidence: 99%